2021
DOI: 10.3991/ijoe.v17i08.24597
|View full text |Cite
|
Sign up to set email alerts
|

A Review on Parameters of Internet Gateway Discovery in MANETS

Abstract: <p class="0abstract"><span lang="EN-US">Mobile ad hoc Networks researchers need to apply specific parameters in the simulation tools chosen to analyze and discuss their results. The challenge faced by multiple authors is on how to decide on the choice of particular parameters. A wrong choice could lead to a no credible result and a doubtful result by other researchers. A best practice is to follow what other authors are using as input parameters in their paper. This review analyses 72 proceeding pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 48 publications
0
2
0
Order By: Relevance
“…Based on Table 11, a comparison is performed to show the progress made in the current survey compared to another recent survey paper [76]. After reviewing the literature contribution, in [76] is the only paper we found that covers the area of interest of the current paper. Another one of the literature contribution was found to be either outdated or partially covered the current area of interest.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on Table 11, a comparison is performed to show the progress made in the current survey compared to another recent survey paper [76]. After reviewing the literature contribution, in [76] is the only paper we found that covers the area of interest of the current paper. Another one of the literature contribution was found to be either outdated or partially covered the current area of interest.…”
Section: Related Workmentioning
confidence: 99%
“…Another one of the literature contribution was found to be either outdated or partially covered the current area of interest. Based on Table 11, a comparison is performed to show the progress made in the current survey compared to another recent survey paper [76]. After reviewing the literature contribution, in [76] is the only paper we found that covers the area of interest of the current paper.…”
Section: Related Workmentioning
confidence: 99%